A phase 2 trial of buparlisib in patients with platinum‐resistant metastatic urothelial carcinoma. Issue 20 (7th August 2020) - McPherson, Victor; Reardon, Brendan; Bhayankara, Aravind; Scott, Sasinya N.; Boyd, Mariel E.; Garcia‐Grossman, Ilana R.; Regazzi, Ashley M.; McCoy, Asia S.; Kim, Philip H.; Al‐Ahmadie, Hikmat; Ostrovnaya, Irina; Roth, Andrew J.; et al.
Abstract : Background: The phosphatidyl 3‐inositol kinase (PI3K)/Akt/mechanistic target of rapamycin (mTOR) pathway frequently is activated in patients with urothelial carcinoma (UC). In the current study, the authors performed a phase 2 study evaluating the efficacy of the pan‐isoform class I PI3K inhibitor buparlisib in patients with platinum‐refractory metastatic UC. Methods: Two cohorts were recruited: an initial genetically unselected cohort and a subsequent expansion cohort of patients with PI3K/Akt/mTOR pathway–altered tumors. The primary endpoint was the 2‐month progression‐free survival rate. A rate of ≥80% was considered promising using a Simon 2‐stage minimax design. Secondary endpoints included safety and correlation of markers of PI3K pathway activation with outcome. Results: Six of 13 evaluable patients within the initial cohort demonstrated stable disease and 1 demonstrated a partial response, which was below the cutoff of 9 patients required to proceed to stage 2. Three of the patients with stable disease and the patient with a partial response harbored somatic TSC1 alterations. Four patients subsequently were recruited onto an expansion cohort: 3 patients with TSC1 alterations and 1 patient with a PIK3CA ‐activating mutation. No patient achieved disease control at 8 weeks and accrual was halted. Of the 19 patients evaluable for toxicity, 17 demonstrated treatment‐related toxicities, 2 of whom had to discontinue therapy. Conclusions: Buparlisib was found to demonstrate modest activity in patients with metastatic UC whose tumors harbored TSC1 loss of function alterations; however, this was not a robust predictor of response to buparlisib. The pattern of genetic coalterations likely influences drug sensitivity. Given the modest clinical activity and substantial toxicity of buparlisib, future trials of PI3K inhibitors in patients with UC should focus on isoform‐selective PI3K inhibitors in genomically selected patients. Lay Summary: The phosphatidyl 3‐inositol kinase (PI3K)/Akt/mechanistic target of rapamycin (mTOR) signaling pathway frequently is upregulated in patients with metastatic urothelial carcinoma (UC). This trial explored buparlisib, an inhibitor of the pathway, in patients with heavily pretreated metastatic UC. Although the drug was found to have modest efficacy, with 6 patients experiencing stable disease and 1 patient achieving a partial response at 8 weeks on therapy, significant side effects also were observed. Patients with specific genetic alterations responded to treatment. Further studies of PI3K pathway inhibition are warranted using newer agents that have superior toxicity profiles and are more selective inhibitors of the pathway. Abstract : Phosphatidyl 3‐inositol kinase (PI3K) pathway inhibition with buparlisib demonstrates modest activity in patients with metastatic urothelial carcinoma, with significant toxicity. Further studies of PI3K pathway inhibition should focus on patients with select genetic alterations and use isoform‐selective inhibitors.